AVALIAÇÃO DA ATIVIDADE ANTIMICROBIANA IN VITRO DA PRÓPOLIS E ÓLEO OZONIZADO EM Staphylococcus pseudintermedius MULTIDROGA RESISTENTE ISOLADO DE OTITE E PIODERMITE SUPERFICIAL DE CÃES - Ana Luiza Zilio (2022)
Among the problems that affect companion animals, dermatoses of bacterial origin have a high incidence in the routine of clinical treatment in Veterinary Medicine. Due to the growing phenomenon of resistance of microorganisms to antimicrobials, the few conventional therapeutic options for the treatment of dogs and cats and aiming to reduce the harmful effects of these skin disorders, the search for therapies with compounds of natural origin has been shown an alternative. The objective of this work was to evaluate the in vitro inhibitory action of the alcoholic extract of brown propolis (30%) and ozonated sunflower oil against multidrug-resistant Staphylococcus pseudintermedius isolated from clinical cases of dermatitis and otitis in dogs. The compounds were tested on 48 bacterial isolates, using the broth microdilution technique. Dilutions of compounds ranging from 1.5% to 100% concentration were used. To verify the in vitro antimicrobial activity of propolis, 48 isolates were exposed to two action times of 1 hour and 24 hours and tested to determine the Minimum Inhibitory Concentration (MIC). The propolis with action in 1 hour presented the variation of the inhibitory concentration between 12.5% and 51 75% and with action in 24 hours between 1.5% and 50%. The bactericidal effect occurred in both times. For ozonated oil, the MIC ranged between 3% and 50%. It is concluded that both compounds have an inhibitory action on multidrug-resistant S. pseudintermedius isolates, which may constitute a future alternative for the treatment of superficial skin infections.